Improving Teacher Professional Competence in Islamic Educational Institutions: A Review of Law No. 14 of 2005 and Related Government Regulations - Puspita Ais Anggraini; Zainap Hartati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Professional competence plays an important role in efforts to improve the quality of education, especially in Islamic educational institutions. This article aims to analyze efforts to develop teacher professional competence from the perspective of Law No. 14 of 2005 concerning Teachers and Lecturers and relevant government regulations. In this study, the method used is a literature study, where data is collected from various sources such as laws, government regulations, journals, and related books. The results of the study indicate that existing regulations provide a clear framework to support the development of professional teachers. However, its implementation requires effective collaboration between the government, educational institutions, and other related parties.